Analysis, Design, and Implementation of a Zero-Voltage-Transition Interleaved Boost Converter - Ting, Naim Suleyman; Sahin, Yakup; Aksoy, Ismail (SPRINGER HEIDELBERG, 2017)
This study proposes a novel zero voltage transition (ZVT) pulse width modulation (PWM) DC DC interleaved boost converter with an active snubber cell. All the semiconductor devices in the converter turn on and off with soft switching to reduce the switching power losses and improve the overall efficiency. Through the interleaved approach, the current stresses of the main devices and the ripple of the output voltage and input current are reduced. The main switches turn on with ZVT and turn off with zero voltage switching (ZVS). The auxiliary switch turns on with zero current switching (ZCS) and turns off with ZVS. In addition, the snubber cell does not create additional current or voltage stress on the main switches and main diodes. The proposed converter can smoothly achieve soft switching characteristics even under light load conditions. The theoretical analysis and operating stages of the proposed converter are made for the D > 50% and D < 50% modes. Finally, a prototype of the proposed converter is implemented, and the experimental results are given in detail for 500 W and 50 kHz. The overall efficiency of the proposed converter reached 95.5% at nominal output power.
Keywords: Hard switching; Interleaved boost converter; Pulse width modulation; Soft switching; Zero voltage transition; AUXILIARY SWITCH; Engineering